Lecture capture affects student learning behaviour. Issue 2 (16th January 2023) - Voelkel, Susanne; Bates, Andy; Gleave, Terry; Larsen, Carl; Stollar, Elliott J.; Wattret, Gemma; Mello, Luciane V.
Abstract : Lecture capture (the real‐time recording of live lectures) has become commonplace in higher education. It is popular with students who like the associated flexibility and believe that lecture recordings improve their grades. Here, we performed a survey ( n = 694, 53% of the cohort) and set up focus groups (2 focus groups, 15 participants) to explore biological sciences students' perceptions of how lecture capture impacts their study behaviour when recordings are provided for every lecture and are made available to students without restriction. The participants in our study were convinced that lecture capture improved their learning, and many students noted that they were dependent on the recordings, thinking that without them, they would not be able to achieve good grades. Students reported that they spend a considerable amount of time watching recordings and making verbatim notes, leaving them little time for independent study. For many, lecture capture seems to reinforce the view that memorisation equals learning, a view that may be reinforced by knowledge‐focussed assessment formats. For most students, lecture capture did not affect self‐reported live lecture attendance patterns. However, about one‐third of the participants reported skipping more classes, and the same participants were more likely to postpone catching up on missed lectures. The outcomes of our study suggest that lecture capture provision may negatively affect some students' attendance and study behaviour, and thus, we suggest more needs to be done to mitigate against this. Abstract : We asked students how lecture capture affects their study habits. Many respondents reported spending a lot of time watching recordings and making detailed notes. Most say that time for other study is diminished, but their attendance pattern is unaffected. Nevertheless, some skip lectures and may not catch up quickly, raising concerns about the negative impact of lecture capture for some.